Kumud – A review: Explore the hidden value of Herb - Kumar, Atul; Priyanka (International Research Journal of Ayurveda & Yoga, 2021)
Kumud, a herb listed in Nighantu under many names, is one of the herbs beneficial to the Rakta and Pitta Doshas. It is a well-known ayurvedic herb with numerous therapeutic benefits. It is also known as the blue lotus, red and blue aquatic plant, star lotus, or manel flower. Indian Blue Lotus is another name for it. It’s native to Asia’s southern and eastern regions, and it’s also Bangladesh and Sri Lanka’s national flower. Utpala is its Sanskrit name. It is a well-known herb that is mentioned in Indian classical texts and used in the Siddha therapeutic system. It’s often utilized in pitta problems because of its bitter taste. It helps to reduce fever and functions as a cooling agent for the body. Along with its traditional applications, many studies have shown it to have hepatoprotective, antioxidant, antidiabetic, DNA protecting, antibacterial, analgesic, and anti-inflammatory properties. The current review focuses on traditional herb’s modern pharmacological activities.